2014
DOI: 10.1016/j.drugalcdep.2014.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation and substance use among adolescents and young adults: A bidirectional relation?

Abstract: Objective To examine reciprocal associations between substance use (cigarette smoking, use of alcohol, marijuana, and other illegal drugs) and suicidal ideation among adolescents and young adults (aged 11–21 at wave 1; aged 24–32 at wave 4). Methods Four waves public-use Add Health data were used in the analysis (N= 3,342). Respondents were surveyed in 1995, 1996, 2001–2002, and 2008–2009. Current regular smoking, past-year alcohol use, past-year marijuana use, and ever use of other illegal drugs as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 30 publications
3
23
1
1
Order By: Relevance
“…Suicidal ideation among undergraduates is associated with various factors. Among the demographic factors, our findings are consistent with previous studies where females were more prone to suicidal ideation [61][62][63][64][65]. However, undergraduates who major in the liberal arts are more likely to experience suicidal ideation than those in medicine.…”
Section: Discussionsupporting
confidence: 91%
“…Suicidal ideation among undergraduates is associated with various factors. Among the demographic factors, our findings are consistent with previous studies where females were more prone to suicidal ideation [61][62][63][64][65]. However, undergraduates who major in the liberal arts are more likely to experience suicidal ideation than those in medicine.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, some studies examining the relation between substance use and SI or SA in the non-TBI literature suggest that these relations are bidirectional and that suicidality may either precede or follow the onset of substance use. 42,43 If drug use at injury in our sample is reflective of premorbid patterns of use, this behavior could be associated with underlying SI prior to the injury, which then persisted through the follow-up period. This idea is consistent with our finding that preinjury SAs are also associated with long-term SI.…”
Section: Discussionmentioning
confidence: 95%
“…This study found that Korean adolescents with suicidal ideation were more likely to engage in multiple HRBs than were those without suicidal ideation. Some studies identified associations between suicidal ideation and single HRBs (Wong, Zhou, Goebert, & Hishinuma, 2013;Zhang & Wu, 2014). Adolescents at risk of suicide tend to experience diverse problems including psychological distress, family dysfunction and impaired peer relationships, which may facilitate adolescent negative coping (Evans, Hawton, & Rodham, 2004).…”
Section: Discussionmentioning
confidence: 99%